Quadruple sulfur and triple oxygen isotope constraints on biological processes in Mars-analog gypsum - Longye Du; Xiaoxiao Yu; Yiliang Li; Xiao Wu; Lin Gong; Gangjian Wei; Qiang Wang; Mang Lin (Geochimica et Cosmochimica Acta, 2026)

Stable neodymium isotopic composition of the upper continental crust through time from ancient glacial diamictites and Holocene marine sediments - Xiaoxiao Yu; Jianghao Bai; Gangjian Wei; Mang Lin; Roberta L. Rudnick (Geochimica et Cosmochimica Acta, 2026)

SlCNR promotes the lycopene accumulation and reduces abscisic acid content in postharvest tomato fruit - Shuai Zhang; Mingzhe Mang; Di Chen; Liqun Ma; Shiyuan Zhang; Tingting Hu; Lin Yu; Jiankang Cao; Daqi Fu; Benzhong Zhu; Hongliang Zhu; Guiqin Qu (Postharvest Biology and Technology, 2026)

Levels of 129I in coastal Pacific Ocean waters from southern California, 2011–2020 and the legacy of Fukushima - A. J. Timothy Jull; Ching-Chih Chang; George S. Burr; Li Cheng; Joellen Russell; Mang Lin; Daniel R. Crocker; Mark Thiemens; Dana Biddulph; Marc W. Caffee; Tom Woodruff; Christopher Glynn; et al. (Frontiers in Marine Science, 2026)
The Fukushima Daiichi Nuclear Power Plant accident released radionuclides directly into the ocean as a result of the Great East Japan Earthquake on March 11, 2011. This material has been transported across the Pacific Ocean and detected in the northeastern Pacific. We began a surface ocean 129 I monitoring program a few months after this disaster in June 2011, with samples from Scripps Pier, La Jolla, California, USA, with the expectation that surface currents originating off the east coast of Japan could eventually carry radionuclides to the La Jolla site. We could not identify a significant distinct signal that can be traced to Fukushima from the record from 2011-2020. We have however recorded a systematic seasonal 129 I time series record that appears to be due to surface circulation variations along the California coast, or perhaps other unexplained effects. We have reported on some of these effects previously, where we summarized results up to 2018. Since then, we have analyzed additional samples obtained during our sampling program for 2018–2020 from Scripps and also report other results collected during 2015–2016 from Newport Beach, CA, which had not been reported. These results support and expand on the previously published dataset.

The high oxygen fugacity of the Chang’e-5 lunar basalt: Implications for redox stratification of the lunar mantle - Jintuan Wang; Hongluo L. Zhang; Le Zhang; Yonghua Cao; Zhendun Qi; Pengli He; Mang Lin; Yi-Gang Xu (Geochimica et Cosmochimica Acta, 2026)

Glacial-interglacial climate modulates sedimentary sulfur cycling in the Peruvian oxygen minimum zone: Mechanistic insights from pyrite multiple sulfur isotopes - Xiaoxiao Yu; Fang Qian; Xiaomin Lin; Longye Du; Jianghao Bai; Dawei Lv; Yanguang Liu; Gangjian Wei; Mang Lin (Geochimica et Cosmochimica Acta, 2025)

Highly oxidized exogenous materials in Chang’e 6 sample returned from the lunar farside South Pole-Aitken basin - Haiyang Xian; Shan Li; Yiping Yang; Jianxi Zhu; Xiaoju Lin; Jiaxin Xi; Wenlin Yang; Yao Xiao; Yonghua Cao; Chenyi Zhao; Miaomiao Zhang; Le Zhang; et al. (Earth and Planetary Science Letters, 2025)

The polarization loss induced by interfacial charge redistribution using Ar plasma treatment in Ni@C composites for superior microwave absorption performance - Jinming Zhang; Mang Niu; Zhaozuo Zhang; Lin Chen; Ruoxin Sun; Zaihao Zhang; Xiaoxia Wang (Chemical Engineering Journal, 2025)

Anaerobic oxidation of methane and greigite formation: Evidence of isotopically heavy pyrite in Pleistocene coastal sediments from the South Yellow Sea - Xiaoxiao Yu; Xi Mei; Jianxing Liu; Baichuan Duan; Rui Zhang; Tiegang Li; Gangjian Wei; Mang Lin (Global and Planetary Change, 2024)

Large magnesium isotopic fractionation in lunar agglutinatic glasses caused by impact-induced chemical diffusion - Le Zhang; Cheng-Yuan Wang; Hai-Yang Xian; Jintuan Wang; Yan-Qiang Zhang; Zhian Bao; Mang Lin; Yi-Gang Xu (Geochimica et Cosmochimica Acta, 2024)

A shallow (<100 km) ilmenite-bearing pyroxenitic source for young lunar volcanism - Chengyuan Wang; Yi-Gang Xu; Le Zhang; Zhiming Chen; Xiaoping Xia; Mang Lin; Feng Guo (Earth and Planetary Science Letters, 2024)

Short-lived natural radionuclides as tracers in hydrogeological studies – A review - Michael Schubert; Mang Lin; Jordan F. Clark; Martin Kralik; Sandra Damatto; Lorenzo Copia; Stefan Terzer-Wassmuth; Astrid Harjung (Science of The Total Environment, 2024)

Holocene climate regulates multiple sulfur isotope compositions of pyrite in the East China sea via sedimentation rate - Xiaoxiao Yu; Xiting Liu; Gangjian Wei; Anchun Li; Mang Lin (Marine and Petroleum Geology, 2024)

Application of an absolute reference frame for methane clumped-isotope analyses - Qingmei Liu; Jiacheng Li; Wenmin Jiang; Yun Li; Mang Lin; Wen Liu; Yanhua Shuai; Haizu Zhang; Ping'an Peng; Yongqiang Xiong (Chemical Geology, 2024)

Interactive effects of dietary leucine and isoleucine affect amino acid profile and metabolism through AKT/TOR signaling pathways in blunt snout bream (Megalobrama amblycephala) - Mang-mang Wang; Yang-yang Huang; Wen-bin Liu; Kang Xiao; Xi Wang; Hui-xing Guo; Yi-lin Zhang; Jing-Wei Fan; Xiang-fei Li; Guang-zhen Jiang (Fish Physiology and Biochemistry, 2024)

40 years of theoretical advances in mass-independent oxygen isotope effects and applications in atmospheric chemistry: A critical review and perspectives - Mang Lin; Mark H. Thiemens (Applied Geochemistry, 2024)

Clinical comprehensive evaluation of direct oral anticoagulants for patients with atrial fibrillation in China - Chi Zhang; Zhi-Chun Gu; Er-Li Ma; Bing-Long Liu; Mang-Mang Pan; Jia Wang; Xin Wang; Bin Wu; Hou-Wen Lin (European Journal of Clinical Pharmacology, 2023)

Feasibility and usability of a mobile health tool on anticoagulation management for patients with atrial fibrillation: a pilot study - Chi Zhang; Mang-Mang Pan; Na Wang; Wei-Wei Wang; Zheng Li; Zhi-Chun Gu; Hou-Wen Lin (European Journal of Clinical Pharmacology, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

The gut-microbiota-testis axis mediated by the activation of the Nrf2 antioxidant pathway is related to prepuberal steroidogenesis disorders induced by di-(2-ethylhexyl) phthalate - Tian-Xin Zhao; Yue-Xin Wei; Jun-Ke Wang; Lin-Dong Han; Mang Sun; Yu-Hao Wu; Lian-Ju Shen; Chun-Lan Long; Sheng-De Wu; Guang-Hui Wei (Environmental Science and Pollution Research, 2020)

Activation of histamine H4 receptor suppresses the proliferation and invasion of esophageal squamous cell carcinoma via both metabolism and non-metabolism signaling pathways - Gong-Hao He; Jia-Qi Ding; Xin Zhang; Wen-Mang Xu; Xiao-Qian Lin; Mei-Jin Huang; Ju Feng; Ping Wang; Wen-Ke Cai (Journal of Molecular Medicine, 2018)

Identification of morin as an agonist of imidazoline I-3 receptor for insulin secretion in diabetic rats - Mang Hung Lin; Chia-Chen Hsu; Jenshinn Lin; Juei-Tang Cheng; Ming Chang Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Characteristics, sources and health risk assessment of toxic heavy metals in PM2.5 at a megacity of southwest China - Youping Li; Zhisheng Zhang; Huifang Liu; Hong Zhou; Zhongyu Fan; Mang Lin; Dalei Wu; Beicheng Xia (Environmental Geochemistry and Health, 2016)

Change of air quality and its impact on atmospheric visibility in central-western Pearl River Delta - Jun-Ming Wan; Mang Lin; Chuen-Yu Chan; Zhi-Sheng Zhang; Guenter Engling; Xue-Mei Wang; Iat-Neng Chan; Shi-Yu Li (Environmental Monitoring and Assessment, 2011)

Recent trends and patterns in breast cancer incidence among Eastern and Southeastern Asian women - Hai-Rim Shin; Clementine Joubert; Mathieu Boniol; Clarisse Hery; Sei Hyun Ahn; Young-Joo Won; Yoshikazu Nishino; Tomotaka Sobue; Chien-Jen Chen; San-Lin You; Maria Rica Mirasol-Lumague; Stephen Chun-Key Law; et al. (Cancer Causes & Control, 2010)

Production of soft rot resistant calla lily by expressing a ferredoxin-like protein gene (pflp) in transgenic plants - Mei-Kuen Yip; Hsiang-En Huang; Mang-Jye Ger; Shih-Hua Chiu; Yuh-Chih Tsai; Chin-I Lin; Teng-Yung Feng (Plant Cell Reports, 2007)

Ferredoxin from sweet pepper (Capsicum annuum L.) intensifying harpinpss-mediated hypersensitive response shows an enhanced production of active oxygen species (AOS) - Badri Venkata Dayakar; Hao-Jan Lin; Cheng-Hsien Chen; Mang-Jye Ger; Bor- Heng Lee; Chia-Hwei Pai; David Chow; Hsiang-En Huang; Shaw-Yhi Hwang; Mei-Chu Chung; Teng-Yung Feng (Plant Molecular Biology, 2003)

cDNA cloning and characterization of a plant protein that may be associated with the harpinPSS-mediated hypersensitive response - Cheng-hsien Chen; Hao-jan Lin; Mang-jye Ger; David Chow; Teng-yung Feng (Plant Molecular Biology, 2000)